2014
DOI: 10.1186/1471-2474-15-229
|View full text |Cite
|
Sign up to set email alerts
|

Comparing lumbo-pelvic kinematics in people with and without back pain: a systematic review and meta-analysis

Abstract: BackgroundClinicians commonly examine posture and movement in people with the belief that correcting dysfunctional movement may reduce pain. If dysfunctional movement is to be accurately identified, clinicians should know what constitutes normal movement and how this differs in people with low back pain (LBP). This systematic review examined studies that compared biomechanical aspects of lumbo-pelvic movement in people with and without LBP.MethodsMEDLINE, Cochrane Central, EMBASE, AMI, CINAHL, Scopus, AMED, IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
227
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 326 publications
(252 citation statements)
references
References 79 publications
20
227
1
4
Order By: Relevance
“…[27][28][29][30][31] A systematic review conducted recently reported a reduction in proprioception along with decrease in ROM and slowed movement in patients with LBP compared with normal counterparts. 32 The results of this study support the link between LBP and proprioception deficits.…”
Section: Introductionsupporting
confidence: 74%
“…[27][28][29][30][31] A systematic review conducted recently reported a reduction in proprioception along with decrease in ROM and slowed movement in patients with LBP compared with normal counterparts. 32 The results of this study support the link between LBP and proprioception deficits.…”
Section: Introductionsupporting
confidence: 74%
“…Movement dysfunctions in patients suffering from diseases such as low back pain (LBP), stroke and Parkinson's disease can be clinically assessed by measuring their trunk range of motion (ROM) and their reaction to specific movement control tasks (Laird et al, 2014;Verheyden et al, 2007;Cole et al, 2010). Specifically, these assessments are comprised of (1) ROM (Laird et al, 2014), (2) movement control impairment (MCI) (Sahrmann, 2002;Luomajoki et al, 2007), (3) repetitive movement (RM) tests (Dideriksen et al, 2014), and (4) tests for proprioception deficits such as reposition error tests (RE) (Rausch Osthoff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there seems to be a lack of normative data which can be used to inform outcomes from intervention to manage spinal pain. A systematic review and meta-analysis by Laird et al (2014), comparing lumbar kinematics in people with and without LBP, concluded that their results do not improve the understanding of the relationship between movement and pain in individuals. They also noted the difficulty in attempting a meaningful interpretation of the data due to the varied methodologies, samples and symptoms reported by the different studies.…”
Section: Discussionmentioning
confidence: 95%
“…Assessing lumbar spine movement in the clinical setting to investigate dysfunction and to monitor changes in spinal movement characteristics of individuals over time, is routine clinical practice (Ha et al, 2013;Laird et al, 2014;Lyle et al, 2005;Maitland, 1997). Single plane movements are often unrepresentative of the actual movements of the lumbar spine, so have limited value in assessing lumbar function (Pearcy and Hindle, 1989).…”
Section: Introductionmentioning
confidence: 98%